Immunohistochemical expression of human epidermal growth factor receptor 2 (HER2/neu) in colorectal carcinoma: experience in a tertiary care hospital of Bangladesh - Syeed, Sifat; Afroze, Nazma; Jannat, Shakila; Ahmed, Mousumi (BIRDEM Medical Journal, 2023)
Background: Among various immunological markers of colorectal carcinoma, the human epidermal growth factor receptor 2 (HER2/neu) is a significant one. Overexpression of HER2/neu in breast cancer has already been established as a poor prognostic marker and trastuzumab (a monoclonal antibody against HER2/neu) has been shown to increase the patient survival. The success of anti-HER2 (Herceptin) therapy in breast cancer has led to the evaluation of HER2/neu expression in colorectal and other cancers. The aim of the study was to determine the expression of HER2/neu in colorectal carcinoma. Methods: This cross-sectional study included 97 diagnosed cases of colorectal carcinoma and was conducted in the Department of Pathology, BIRDEM General Hospital, Dhaka from September 2018 to August 2020. Sections were taken from paraffin blocks for routine hematoxylin and eosin (H&E) stain and immunohistochemical stain with HER2/neu antibody. Relevant clinical and microscopic data including age, sex, tumor site and tumor size were collected and recorded. Results: HER2/neu expression was observed in 47.4% (46) cases in this study. Among which 28.9% cases were found strongly positive (Score 3+) and 18.6% cases were found weakly positive (Score 2+). The mean age of colorectal carcinoma patient was 50.54±14.32 years and the highest expression of HER2/neu was found in 21- 30 years age group. The tumor was mostly (66.0%) located in the colon whereas HER2/neu expression was more in rectum (54.5%). The tumor size was ³5 cm in 64.9% cases while positive expression of HER2/neu was more in tumors <5 cm in size (50.0%). No statistically significant correlation of HER2/neu expression was found with age, sex, tumor site and size. Conclusion: Expression of HER2/neu has been observed in nearly half of colorectal carcinoma patients with strongly positive in almost 29% cases. BIRDEM Med J 2023; 13(2): 81-87